Atomically Fe doped hollow mesoporous carbon spheres for peroxymonosulfate mediated advanced oxidation processes with a dual activation pathway. Issue 38 (7th September 2022) - Wang, Qing; Liu, Xiaomei; Cai, An; He, Hongwei; Zhang, Guoliang; Zhang, Fengbao; Fan, Xiaobin; Peng, Wenchao; Li, Yang
Abstract : The introduction of atomically dispersed Fe atoms can modulate the PMS activation pathway; that is, the radical-mediated process of PMS activation accelerated by graphitic N is attenuated, in turn boosting electron-transfer-mediated nonradical processes. Abstract : PMS-based advanced oxidation processes (AOPs) are a high-efficiency and economically favorable approach for dealing with aqueous organic pollutants. In this work, an Fe single-atom catalyst deposited on N-doped hollow mesoporous carbon spheres (Fe–NC HMCS) is prepared via an in situ hard-template strategy and used to activate peroxymonosulfate (PMS) for organic pollutant degradation. Benefiting from the presence of Fe–N sites and a suitable structure (a large specific surface area and a uniform mesoporous structure), the obtained Fe–NC HMCS catalyst with a low Fe-loading capacity (0.16 wt%) exhibits an outstanding turnover frequency (TOF) as high as 55.4 min −1 during the degradation of bisphenol A (BPA). Remarkably, the introduction of atomically dispersed Fe atoms can successfully modulate the pathway of PMS activation, and the radical-mediated process of PMS activation accelerated by graphitic N is attenuated, in turn boosting electron-transfer-mediated nonradical processes. This work provides an ingenious strategy for designing highly efficient and selective single-atom catalysts and reveals the corresponding activation mechanism for PMS-based AOPs.